ECOSYSTEM-BASED APPROACH TO NORWEGIAN AQUACULTURE MANAGEMENT - Alaliyat, Saleh (European Scientific Journal, ESJ, 2014)
The Norwegian aquaculture is a growing industry and has become an important industry in Norway. It is one of the most export industries, and contributes to activities throughout the whole country, particularly in many local communities along the cost where the aquaculture industry activity is concentrated. Poor management and unregulated aquaculture industry will lead to many negative effects on the whole ecosystem. The ecosystem has thresholds and limits that can affect the system structure when exceeded. The ecosystem approach for aquaculture is a strategy for the integrated management of land, water, and living resources that it promotes sustainable development, equity, and resilience of interlinked social and ecological systems. Aquaculture development needs to be within the carrying capacity of the water resources, social-based and within other relative sectors so that is sustainable without negative impacts on the environment. In this paper, I will discuss an applying ecosystem-based approach to Norwegian aquaculture at different scales to ensure a sustainable aquaculture development without negative impacts on the environment.